Experiments in the use of Pheno-barbital-sodium for complete anaesthetization of Ambylrhynchus cristatus - Von Hagen, Wolfang (1936)
This study explores the use of Pheno-barbital-sodium (Nembutal) to achieve complete anaesthetization of the Marine Iguana (Ambylrhynchus cristatus) native to the Galapagos Islands. The Marine Iguana, a seaweed-eating reptile adapted to the lava-strewn shores, is difficult to handle due to its tenacity and defensive behavior. The author successfully administered intramuscular injections of Nembutal to immobilize the iguanas without mortality, allowing detailed observation of their physiology and parasitic ticks. The sedation also enabled forced feeding by relaxing the jaw muscles, overcoming a major challenge in keeping these iguanas alive in captivity, as they typically refuse to eat or open their mouths. The study provides valuable data on the effects of this sedative on cold-blooded animals and offers a practical method for handling and maintaining Marine Iguanas for research and conservation purposes.